The effect of adding rice straw charcoal to the processing of bio-pellet from cacao pod husk - Retno Damayanti; Sandra Sandra; Novita Riski Nanda (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
Cacao pod husk and rice straw charcoal are potentially transformed into bio-pellet because of their high calorific value. Cocoa pod husk and rice straw charcoal has a calorific value of 4974.837 cal/g and 3569.837 cal/g, respectively. This research aimed to identify the effect of variations in particle size and in the addition ratio of rice straw charcoal on the calorific value of bio-pellet. Randomized block design factorial were employed in this study with factor of the addition ratio of rice straw charcoal and cacao pod husk (i.e. 0%:100%, 20% : 80%, 40% : 60%) and the particle size (i.e. 20, 40, 60 and 80 mesh). The results showed that rice straw charcoal addition resulted bio-pellet with the calorific value of 4111.93 – 4706.57 cal/g, and fulfill the SNI of bio-pellet (SNI 8021-2014). The treatment with addition of 100% cocoa pod husk and 80 mesh particle size generated the superior quality of bio-pellet. The findings confirmed that addition of rice straw charcoal did not enhance the energy potential (i.e. calorific value) of the bio-pellets, hence it is unfavourable option.